THE GENDER RELATION AND STUDENT ORGANIZATION (A RESEARCH OF WOMAN INVOLVEMENT IN DECISION MAKING AT DEMA FACULTY IN IAIN BUKITTINGGI - Redni Putri Meldianto; Silfia Hanani (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Gender inequality occurs in the form of marginalization, subordination, stereotype, violence, and double burden happened in every social institution, one of which is the DEMA Faculty at IAIN Bukittinggi. The difference in gender roles between male students and female students in various Faculty DEMA activities in the IAIN Bukittinggi environment causes inequality in gender relations, due to the limited space owned by female students. Meanwhile, the sexist division of labor is based on gender, where male students play a role in broader activities, and female students are only tasked with taking care of correspondence and finances within the organization. The research method used is descriptive qualitative with data collection techniques, interviews, and documentation, the analysis used is Miles and Huberman data analysis techniques. For the data obtained to be accurate, data validity techniques were carried out by extending observations, increasing persistence, and triangulation. The results of the study can be described that the conditions that occur in the Faculty DEMA in the IAIN Bukittinggi environment place male students as superiority and female students as inferiority so that it is very detrimental to the position of female students in the policymaking process at the Faculty DEMA in the IAIN Bukittinggi environment. Which results in inequality in gender relations, because of the understanding that men must be in the top position in policymaking. The form of inequality in gender relations that occurs in DEMA Faculties in the IAIN Bukittinggi environment, such as marginalization, stereotypes, and subordination. Strongly rooted in a patriarchal culture that always puts men as the central figure in gender relations, so that female students are always the second class and get less professional treatment in organizational reality and the weak pattern of gender relations in DEMA Faculty in IAIN Bukittinggi, and less open in the context of the relationship between the two, also affects the effectiveness of the organization.